Tribological Performance of Gd-DLC and Eu-DLC Coatings in the Presence of Synthetic Oils Containing Ionic Liquid Additives - Omiya, T. (2023)
The lubrication of gadolinium-doped diamond-like carbon (Gd-DLC) and europium-doped diamond-like carbon (Eu-DLC) coatings with trihexyltetradecylphosphonium bis(2-ethylhexyl) phosphate ([P66614][DEHP]) ionic liquid (IL) as 1 wt% additive in polyalphaolefin (PAO) 8 was studied. The results of the friction tests under boundary lubrication conditions showed that Gd-DLC and Eu-DLC coatings in the presence of the IL exhibit a friction reduction, especially with the high atomic concentration of doped metal. Later, the surface observation after the long-term wear test indicated that Gd-DLC coatings have less abrasive wear and higher anti-wear properties compared to Eu-DLC coatings due to the enhanced formation of tribofilms derived from the phosphorus of the IL on the steel ball as the counter body. From these results, we have concluded that the friction reduction and the anti-wear property in the presence of the IL can be improved by changing the type and the concentration of the doped metals. This clearly shows that the novel lubrication system combining the Gd-DLC and Eu-DLC coatings with the IL allows for guiding future research and development.